Where has carbon footprint research gone?. (January 2021) - Chen, Ru; Zhang, Ruoyan; Han, Hongyun
Graphical abstract: Highlights: The research fronts and intellectual bases of carbon footprint (CF) research. A case study of using progressive knowledge domain visualization of the CiteSpace. The Chinese Academy of Sciences represented the core force of CF research. Six emerging fronts topics in the historical evolution of CF research. CF showed great vitality in the cross-application of agriculture and energy. Abstract: Carbon footprint (CF) stands for a professional term is widely used in the public domain to cope with the threat posed by climate change. With obtained 9848 records of literature information from the database of Web of Science, a bibliometric analysis was implemented to judge the knowledge domain structure and evolution of frontiers in CF research by using the CiteSpace to make up for the lack of previous reviews. The results showed that the CF research was concentrated in the fields of Engineering, Environmental sciences ecology, Science technology other topics, Energy fuels, Computer science and Business economics, and there is a significant cooperative relationship between researchers, especially those with a high volume of publications. The regional layout of intercontinental CF research forces was Europe, North America, and Asia, while that between countries were the United States of America, China, England, Australia and Italy, specifically, the Chinese Academy of Sciences showed the core force of CF research with a high volume of publications and strong cooperation with international institutions. The debate and application of CF accounting method, Case Studies of CF for livestock and its products production, CF estimation for the final consumption of goods and services, Impact of human food consumption on the climate change, Application of Footprint Family for sustainable development, and CF estimation for household consumption and its drivers were the emerging CF research fronts in historical evolution. Therefore, the CF research has its own characteristics in terms of spatial and temporal layout, cooperation intensity and knowledge hierarchy, and the related topics of cross-application of agriculture and energy are becoming the potential frontier of future research. This work not only provides the possible innovative directions, but also a reliable reference for the rapid and comprehensive understanding of CF research for the novices.